1958
DOI: 10.1099/00221287-19-2-407
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Aberrancy in Growth of Some Bacillus megaterium Strains

Abstract: SUMMARY: Two hundred strains of Bacillus megatmiurn recently isolated from soil were tested for an antagonistic effect on a phage-resistant strain of the same species. Fifty-one strains gave a zone of inhibition on a lawn of the indicator strain. This effect was increased by a small dose of ultraviolet radiation which also caused 41 other strains to show an antagonistic effect. Sixteen strains which were completely lysed after U.V. irradiation also produced confluent lysis of the indicator strain. When grown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1960
1960
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 4 publications
(1 reference statement)
0
19
0
Order By: Relevance
“…Approximately 14% of the MegAmutants of strain VT100 (a MegA+ MegC+ derivative of strain 216 cured for pBM106) were also MegC-after mitomycin C enrichment. Mutants cured of the ability to produce either megacin A-216 or megacin A-19213 failed to show characteristic lysis (19,22) upon mitomycin C induction (data not shown).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Approximately 14% of the MegAmutants of strain VT100 (a MegA+ MegC+ derivative of strain 216 cured for pBM106) were also MegC-after mitomycin C enrichment. Mutants cured of the ability to produce either megacin A-216 or megacin A-19213 failed to show characteristic lysis (19,22) upon mitomycin C induction (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…Isolation of Megderivatives of B. megaterium strains 216 and ATCC 19213. The lysis of megacin A-producing bacteria after induction of megacin production (21,22) was exploited to enrich for spontaneously occurring MegA-bacteria. Early log-phase cultures of B. megaterium growing at 37°C in yeast extract-tryptone broth (32) were induced with 1 p.g of mitomycin C per ml at an initial cell density corresponding to 15 to 30 Klett units (red filter).…”
Section: Methodsmentioning
confidence: 99%
“…The kinetics of production as well as the characteristics, the antibacterial spectrum and the mode of action of the bacteriocin studied by us, allow us to rule out its identity with any of those listed abovel). Rather, it appears to be similar or identical with megacin A which is a bacteriocin of B. megaterium produced by about 5 % of its strains occurring in nature (IV~~NOVICS and NAGY 1958). A prototype of megacinogenic strain 216 (IV~~NOVICS 1965) produces a bacteriocin which was identified with phospholipase A (OZAKI et al 1966), liberating unsaturated fatty acids from egg yolk lecithin located at 8-position (OCHI et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-two non-megacinogenic mutants derived from megacinogenic parents could not be made to lyse by exposure to U.V. irradiation (Ivanovics & Nagy, 1958). Electron microscope studies of active lysates failed to demonstrate the presence of any phage particles, and it was concluded that the bacteriocinogenic character of Bacillus megaterium was not associated in the slightest degree with phage production (Ivanovics, Alfodi & Lovas, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to secure such a mutant by U.V. irradiation (Ivanovics & Nagy, 1958) or with cobalt chloride and acriflavine (Hirota, 1956(Hirota, , 1957Furness & Rowley, 1957) were unsuccessful. Also bacteria which survived heat treatment (Zamenhof 8: Greer, 1958) or which had passed through the protoplast state did not lose the colicinogenic property.…”
Section: The Nature Of Colicin-15mentioning
confidence: 99%